Colonic Microbiota and Metabolites Response to Different Dietary Protein Sources in a Piglet Model - Li, Rui; Chang, Ling; Hou, Gaifeng; Song, Zehe; Fan, Zhiyong; He, Xi; Hou, De-Xing (Frontiers in Nutrition, 2019)
Dietary protein source have the potential to affect the colon microbiome of weaned piglets that will have a large impact on its metabolic capabilities and hindgut health. This study aimed to explore the effects of different protein sources on growth performance, colonic microbiome and microbial metabolites in weaning pigs. Twenty-four individually housed male piglets (Landrace × Yorkshire; initial BW = 12.61 ± 1.45 kg) were randomly divided into four isoenergetic and isonitrogenous semi-purified diets containing Palbio 50 RD (P50), Soyppt-50% (S50), concentrated degossypolized cottonseed protein (CDCP) and fish meal (FM) as the sole protein sources. After a 10-day trial period, all pigs were humanely killed to collect colonic digesta samples for microbiome and metabolites analysis. Experimental diets did not affect ADG, but P50 increased fecal scores compared with S50 and CDCP. 13, 74, 39 and 31 unique OTUs were indentified in P50, CDCP, FM and S50 by Venn analysis, respectively. Protein sources did not change colonic bacterial richness or diversity as analyseded by alpha diversity. Firmicutes, Bacteroidetes, Proteobacteria and Spirochaetes were the predominant phyla of four groups, and Firmicutes/Bacteroidetes ratio in CDCP, S50, P50 and FM was gradually reduced. At genus level, P50 and FM had high Escherichia and Clostridium abundance, CDCP owned great abundant of Lactobacillus and Megasphaera, S50 consisted of high Gemmiger abundance. Greater variations were seen in P50 and FM compared with CDCP and S50. CDCP had a trend to elevate valeric acid and BCFA concentrations compared with other diets. P50 and FM had greater ammonia nitrogen and methylamine contents than S50 and CDCP. These discoveries suggested that short-term feeding differnet protein sources did not affect piglets growth, but P50 increased diarrhea. Potential pathogenic bacteria and detrimental metabolites appeared in colon of pigs fed P50 and FM, while beneficial effects appeared in pigs fed CDCP and S50, indicating that available plant protein added to weaned pigs diet is good for colon health via reducing protein fermentation.